Radical Prostatectomy with Extended Pelvic Lymphadenectomy: Impact of Separate Vs. En Bloc Lymph Node Submission on Pathohistological Analysis - Dorian Srok; Gordana Đorđević; Dean Markić; Josip Španjol; Kristian Krpina (Acta Clinica Croatica)
Introduction: In prostate cancer (PC), it is well established that the wider the anatomical template of dissection, the higher the number of lymph nodes (LNs) retrieved, and the higher the nodal yield, the better the detection of metastasis1,2. Objectives: The objectives of this study were to evaluate if the change in submission methodology (en bloc vs. separate) had an impact on the number of total LNs identified per patient and the number of positive LNs found, and to determine the impact of individual pathologists on the number of total LNs and positive LNs. Patients and methods: We performed a retrospective analysis of hospital records of patients with PC in whom radical prostatectomy (RP) with pelvic lymphadenectomy (PLND) was done in the period from November 2012 to December 2018. We used only a single-surgeon series in order to avoid performance bias in the lymphadenectomy template. Pathohistological examinations were performed by our hospital’s two dedicated urogenital pathologists. Patients were divided into high and intermediate risk groups according to the European Association of Urology (EAU) guidelines, based on submission methodology of the lymphadenectomy tissue and by the pathologist performing the examinations. The number of LNs and number of positive LNs acquired were then compared using the Mann-Whitney test. Results: Patients who underwent separate submission of lymphadenectomy tissue had a significantly higher nodal yield, but there was no difference in the number of positive LNs. There was no significant difference in the total number of LNs acquired and LN metastases detected between our two pathologists when comparing them by submission technique. Conclusions: Separate submission of lymphadenectomy tissue resulted in a higher nodal yield, but it did not translate to a higher number of positive LNs found.